2019
DOI: 10.1155/2019/9048239
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative ‘STEMI’ in Intracerebral Hemorrhage due to Arteriovenous Malformation: A Case Report and Review of Literature

Abstract: Electrocardiogram (ECG) changes suggestive of cardiac ischemia are frequently demonstrated in patients with ischemic stroke and subarachnoid hemorrhage. However, little is known of such changes particularly acute ST segment myocardial infarction (STEMI) in patients with intracerebral hemorrhage (ICH), especially after neurosurgery. We present a patient with intraparenchymal hemorrhage due to cerebral arteriovenous malformation (AVM) who exhibited acute STEMI after neurosurgery. Serial cardiac biomarkers and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…For ruptured AVMs, it may be preferable to reverse anticoagulation at the end of the case. This can be confounded, however, by the effect of intracranial hemorrhage on electrocardiographic findings that can simulate myocardial infarction 51…”
Section: Disease-specific Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For ruptured AVMs, it may be preferable to reverse anticoagulation at the end of the case. This can be confounded, however, by the effect of intracranial hemorrhage on electrocardiographic findings that can simulate myocardial infarction 51…”
Section: Disease-specific Considerationsmentioning
confidence: 99%
“…This can be confounded, however, by the effect of intracranial hemorrhage on electrocardiographic findings that can simulate myocardial infarction. 51 For high-flow AVMs, particularly in the setting of AVM rupture, physicians may choose not to use routine intraprocedural systemic heparinization on the assumption that the high flow will mitigate against thrombus formation on endovascular catheters in feeding arteries. For unruptured pediatric highflow arteriovenous fistulas, however, a case study has identified jugular venous outflow stenosis or occlusion as a risk factor for post-embolization cerebral venous thrombosis.…”
Section: Standards Recommendation 6: For Patients With Atrial Fibrill...mentioning
confidence: 99%